A fully humanized IgG-like bispecific antibody for effective dual targeting of CXCR3 and CCR6. - Remy Robert; Laurent Juglair; Ee X Lim; Caroline Ang; Carl J H Wang; Gregor Ebert; Olan Dolezal; Charles R Mackay (PLoS ONE)
Chemokines and their receptors are pivotal for the trafficking of leukocytes during immune responses, and host defense. However, immune cell migration also contributes to a wide variety of autoimmune and chronic inflammatory diseases. Compelling evidence suggests that both CXCR3 and CCR6 chemokine receptors play crucial roles in the migration of pathological Th1 and Th17 cells during the course of certain inflammatory diseases. The use of two or more receptors by pathogenic cells may explain why targeting of individual receptors has proven disappointing in the clinic. We therefore hypothesized that simultaneous targeting of both CXCR3 and CCR6 with a bispecific antibody (BsAb) might result in decreased chemotaxis and/or specific depletion of pro-inflammatory T cell subsets. In this study, we designed and characterized a fully humanized BsAb. We show that the BsAb binds to both chemokine receptors, as demonstrated by Flow Cytometry and Surface Plasmon Resonance analysis. Furthermore, we demonstrate that the BsAb effectively blocks cell chemotaxis and induces specific antibody-dependent cell-mediated cytotoxicity (ADCC) in vitro. Therefore, we propose that dual targeting of CXCR3 and CCR6 with a fully humanized BsAb may display a potent interventional approach for the treatment of inflammatory and autoimmune diseases.